Pengaruh Manajemen Sarana Dan Prasarana Terhadap Kualitas Proses Pembelajaran Siswa Kelas XII Di SMK Negeri 1 Siborongborong Tahun 2025 - Lolyani Turang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine the effect of facilities and infrastructure management on the quality of the learning process of twelfth-grade students at State Vocational High School 1 Siborongborong in 2025. The method used in this research is a quantitative inferential statistical approach. The population consisted of all twelfth-grade students totaling 43 individuals, and the sample was also 43 individuals, selected using purposive sampling techniques. Data were collected through a closed-ended questionnaire consisting of 30 items. The results of the data analysis indicate that there is a positive and significant effect of facilities and infrastructure management on the quality of the learning process of twelfth-grade students at SMK Negeri 1 Siborongborong. This is shown by the following findings: the normality test yielded an asymp. Sig. (2-tailed) value of 0.200, which is greater than 0.05, and the linearity test showed a significance value for deviation from linearity of 0.131, also greater than 0.05. In hypothesis testing, the correlation test between variables X and Y resulted in rxy = 0.621, which is greater than rtable = 0.301, indicating a positive relationship between the two variables. The significance test showed tcount = 5.075, which is greater than ttable = 2.021, indicating a significant relationship between variables X and Y. The regression equation obtained was Ŷ = 7.850 + 0.373X, and the coefficient of determination (r²) was 62.1%. Furthermore, the F-test showed that Fcount = 25.752 is greater than Ftable = 4.08. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Keywords: Facilities and Infrastructure Management, Quality of the Student Learning Process.